Trimodality Therapy for Bladder Preservation in the Elderly Population with Invasive Bladder Cancer - Turgeon, Guy-Anne; Souhami, Luis (Frontiers in Oncology, 2014)
Bladder cancer is considered as primarily a disease of the elderly, typically aged in their 70s or 80s and often with associated medical comorbidities. Unfortunately, fewer elderly patients receive radical treatment for muscle-invasive bladder cancer (MIBC) that their younger counterparts. Over the last decades, several studies have shown that the use of trimodality therapy consisting of transurethral bladder resection followed by concomitant chemotherapy and radiation therapy results in comparable outcomes to radical cystectomy, considered the gold standard for this disease. In this review, we revised the literature on bladder-preservation treatments using the trimodality approach in the elderly population with MIBC.